Global Environmental Nontuberculous Mycobacteria and Their Contemporaneous Man-Made and Natural Niches - Honda, Jennifer R.; Virdi, Ravleen; Chan, Edward D. (Frontiers in Microbiology, 2018)
Seminal microbiological work of environmental NTM includes the discovery that NTM inhabit water distribution systems and soil, and that the species of NTM found are geographically diverse. It is likely that patients acquire their infections from repeated exposures to their environments, based on the well-accepted paradigm that water and soil bioaerosols – enriched for NTM – can be inhaled into the lungs. Support comes from reports demonstrating NTM isolated from the lungs of patients are genetically identical to NTM found in their environment. Well documented sources of NTM include peat-rich soils, natural waters, drinking water, hot water heaters, refrigerator taps, catheters, and environmental amoeba. However, NTM have also been recovered in biofilms from ice machines, heated nebulizers, and heater-cooler units, as well as seat dust from theatres, vacuum cleaners, and cobwebs. New studies on the horizon aim to significantly expand the current knowledge of environmental NTM niches. Specifically, the Hawaiian Island environment is currently being studied as a model to identify other point sources of exposure as it is the U.S. state with the highest number of NTM lung disease cases. Because of its geographic isolation and unique ecosystem, the Hawaiian environment is being probed for correlative factors that may promote environmental NTM colonization.